Factors Affecting Personal Income Tax Compliance in Kawasoti Municipality - Lamsal, Bishnu Prasad (Madhyabindu Journal, 2026)
Government revenue is a major concern and it relies heavily on taxation because it helps in financing of government services, development of infrastructure, and social welfare programs that are essential sources of stability to the economy. The purpose of the research was to evaluate the current status of personal income tax compliance (PITC), measure the links and influences of taxpayer attitude, tax expertise, and social norms with fines and penalties on the compliance. The research methodology applied was the quantitative research design that gathers the primary data in the form of a structured questionnaires given to 316 individual taxpayers in Kawasoti Municipality by means of purposive sampling. The analysis of data were made through descriptive statistics, correlation and regression analysis through SPSS. Some of the major findings indicate that the attitude of taxpayer, knowledge of tax and fines and penalty strongly and positively influence the determination of personal income tax. This implies that optimistic views towards taxpayers, good familiarity to the tax laws, and effective enforcement tools promote compliance. On the opposite, the effect of social norms in this situation was evaluated as having no statistical significance in determining compliance. According to the study, the focus should be on taxpayer education that would lead to positive attitudes, enforcement of penalties and augmenting of the rates of compliance to generate more revenue and facilitate equitable resource allocation by the policymakers.